Strategi literasi internet ramah anak dalam upaya mengurangi dampak kejahatan di media sosial pada yayasan yatim dan dhuafa Al-Jannah, Tangerang Selatan - Sumarni, Lilik; Yuningsih, Siska; Swarnawati, Aminah; Firmansyah, Khalid (STAI Auliaurrasyidin Tembilahan, 2025)
The widespread use of the internet among children without adequate supervision increases their risk of exposure to harmful content, such as cyberbullying, hoaxes, pornography, and digital addiction. A similar challenge was observed at the Al-Jannah Orphan and Underprivileged Foundation in South Tangerang, which oversees 23 foster children under the care of four guardians with limited digital literacy. To address this issue, a community engagement program was implemented, incorporating counseling, role-play, and empathy-based digital parenting training. Post-intervention assessments revealed significant improvements, with a 39% average increase in children’s understanding of digital ethics and a 46% average rise in caregivers’ readiness to supervise online activities. This initiative not only impacted individuals but also fostered a transformative shift toward a more supportive digital caregiving ecosystem. The program is expected to serve as a sustainable model for digital literacy mentoring in similar care institutions, cultivating an ethical, resilient, and digitally savvy generation.